1977
DOI: 10.2105/ajph.67.10.940
|View full text |Cite
|
Sign up to set email alerts
|

Statutory authorizations for the work of local health departments.

Abstract: [940][941][942][943][944][945] 1977) sibilities to state health agencies, which may be empowered to write regulations that further delegate these responsibilities to local health agencies; statutes that grant powers to other governmental units, especially at the local level such as county governments, which then enact regulations that define the work of local health agencies; appropriations that carry authorizations through any of the previously identified channels. Developing a full understanding of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Eighty-eight percent of the responding agencies reported a clinical component. Many of these clinical dental programs are specifically authorized in either state or local statutes (7). While preventive and basic restorative dental procedures are provided by the overwhelming majority of the agencies, prosthetic (fixed and removable), orthodontic, and periodontal care are provided by less than half.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-eight percent of the responding agencies reported a clinical component. Many of these clinical dental programs are specifically authorized in either state or local statutes (7). While preventive and basic restorative dental procedures are provided by the overwhelming majority of the agencies, prosthetic (fixed and removable), orthodontic, and periodontal care are provided by less than half.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies by Miller and colleagues during the 1970s and 1980s (10,13,(24)(25)(26) provided new insights into the public health infrastructure and the effect of various forces on LHDs. Despite Hanlon's call, these studies largely supported the need for LHDs to provide personal health care services within their communities.…”
Section: Measurement Of Local Public Healthmentioning
confidence: 99%
“…At the state level, no recent information is available regarding oral health programs for older adults. Miller et al reported that 50 percent of state health agencies were authorized by state public health statutes to provide dental health services (19). In a 1983 study, 20 state health agencies reported the existence of special initiatives in geriatric dentistry, excluding direct clinical services (20).…”
mentioning
confidence: 99%